Factors associated with anemia in chronic kidney disease in the Brazilian population: national health survey - de Sousa, Letícia Cristina Machado; Rabello Silva, Nathalia; Uliana Picolo, Bianca; Pádua Netto, Marcus Vinícius de; Saraiva da Silva, Luciana (Frontiers in Nutrition, 2026)
IntroductionChronic kidney disease (CKD) is a public health issue often accompanied by anemia from its early stages. Identifying associated factors is essential, especially given the limited data on the Brazilian population and the outcomes of anemia among individuals with CKD.ObjectiveTo investigate the factors associated with anemia in individuals with CKD in the Brazilian population.MethodsA cross-sectional study was conducted using the 2013 National Health Survey (PNS) laboratory database. Socioeconomic, demographic, and clinical variables (sex, age, education, race/color, nutritional status, arterial hypertension (AH), diabetes mellitus (DM), hypercholesterolemia, cardiovascular disease (CVD), smoking, and excessive alcohol consumption) were evaluated. Associations between anemia and the stages of CKD were examined using multivariable logistic regression models.Results8,952 individuals were evaluated. The prevalence of anemia in the total population was 10.1%, and in the population with CKD, it was 15.1%. Anemia was found to be more prevalent among women, older adults, individuals with lower educational, and those of mixed and black race/color. In the fully adjusted model, women (OR 1.59; CI, 1.35–1.88), black individuals (OR 1.76; CI, 1.36–2.26), and those with AH (OR 1.26; CI, 1.04–1.52) or DM (OR 1.30; CI, 1.00–1.69) exhibited a higher likelihood of anemia. Conversely, individuals with higher educational levels (OR 0.65; CI, 0.49–0.87), smokers (OR 0.71; CI, 0.56–0.91) those with a eutrophic body status (OR 0.66; CI, 0.49–0.90), and obese individuals (OR 0.49; CI, 0.36–0.67) had lower likelihood of anemia compared to underweight individuals. Individuals with advanced stages of CKD had a higher likelihood of anemia compared with those in early stages, and this association remained significant after adjustment for sociodemographic and clinical variables, with the highest odds observed in stages 4 and 5.ConclusionThis study made it possible to identify the variables related to the presence of anemia in the different stages of CKD, such as AH, DM, sex, education, race/color, and nutritional status.